When Women Come First : Gender and Class in Transnational Migration - George, Sheba Mariam, 1966- (Book collections on Project MUSE., 2005)
With a subtle yet penetrating understanding of the intricate interplay of gender, race, and class, Sheba George examines an unusual immigration pattern to analyze what happens when women who migrate before men become the breadwinners in the family. Focusing on a group of female nurses who moved from India to the United States before their husbands, she shows that this story of economic mobility and professional achievement conceals underlying conditions of upheaval not only in the families and immigrant community but also in the sending community in India. This richly textured and impeccably r.